Evaluación del control interno y su incidencia en la valoración del riesgo de la CIA. INTERDATOS S.A. del cantón Babahoyo - Espinoza Pambaya, Oscar Eduardo (2021)
The internal control within the company is very important, because thanks to it risks and frauds are avoided, in addition the assets and interests of the entity are protected and taken care of, allowing to evaluate the efficiency of the same one as far as its organization is concerned. At the moment of the evaluation of the internal control, the management of its five components is executed, which allow to carry out tests of effectiveness of its systems, either administrative or accounting, with the purpose of providing a reasonable security on the operative and financial processes of the entity, in order to assure the fulfillment of the objectives and goals of the same one.